Osnovna merjenja : Uvod v merske napake in kvantitativno analizo fizikalnih meritev - Dobovišek, Andrej (University of Maribor Press, 2021)
Basic Measurements: Introduction to Measuring Errors and Quantitative Analysis of Physical Measurements. The purpose of the publication is to provide students with basic knowledge in the field of measurement errors and their use in the analysis of physical measurements in the most clearest, transparent and systematic way. The booklet describes the basic approaches to drawing and reading diagrams by taking into account measurement errors. As a teaching material, the booklet is intended for first-year physics students in the compulsory subject Basic Measurements and for physics students in the study program Physics Teacher in Laboratory Exercises in Mechanics. Experience shows that basic knowledge in the field of drawing and analysis of diagrams by taking into account measurement errors are, for the study of physics, so important that it makes sense to put more emphasis on this subject and treat it very systematically, as well as to consolidate knowledge with some additional theoretical exercises. The first part of this booklet follows these requirements. The second part describes 7 laboratory exercises that students carry out on their own in the physical laboratory.